DAMPAK PERKEMBANGAN PARIWISATA LHOKNGA TERHADAP MASYARAKAT MON IKEUN - Adhica Perkasa; Izziah Izziah; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2020)
Based on data from Disbudpar (2017), the low quality of human resources and the lack of indigenous knowledge on tourism management are the main obstacles for indigenous people in the Lhoknga beach tourism area to be directly involved in the tourism sector. Even though the data shows the behavior of tourists who damage the environment by littering, the behavior of indigenous people who live in the tourist area of Lhoknga beach, not all of them show a caring attitude towards the natural environment. Regarding the issue of infrastructure in the Lhoknga coastal tourism area such as clean water, electricity and tourism transportation in the region is still an obstacle where with the increasing number of tourists each year, improvement of infrastructure is also very important to be done to provide better services to tourists (Disbudpar Aceh Besar, 2017 ). Therefore, research is needed to describe the issues in the Lhoknga beach tourism area in the form of tourism development with a focus on the attitudes and desires of local communities towards tourism development. The purpose of this research is to determine the impact of Lhoknga tourism development on Gampong Mon Ikeun. This research method plan will use qualitative methods to explain its development. The research location was conducted at Gampong Mon IKeun, Lhoknga beach tourism area. It is hoped that later this research will have a positive impact on Gampong Mon Ikeun on the development of the Lhoknga tourism area.